Leighs disease: powerhouse failure - Himanshu Dua; Radhika Mantry (MRIMS Journal of Health Sciences, 2018)
Leigh disease, also known as juvenile sub acute necrotizing encephalomyelopathy, Leigh syndrome, infantile sub acute necrotizing encephalomyelopathy, and sub acute necrotizing encephalomyelopathy (SNEM), is a rare inherited neurometabolic disorder that affects the central nervous system. A five months old male child born out of non-consanguineous marriage was in regular follow up with a pediatrician in view of birth history of full term, low birth weight. Records showed steady weight gain with gross motor delay and central hypotonia. 15 days prior to admission, child had rhinorrhea, cough, hoarseness and intermittent stridor which were initially treated with oral medication. Subsequently the child developed fever for which he was admitted and treated with antibiotics. Complete blood count, C reactive protein, blood culture, CSF was normal. X-ray showed hyperinflation. The child then developed features of encephalopathy with myoclonic jerks. In view of history of developmental delay and clinically central hypotonia, with investigations pointing towards non-infective etiology, a possibility of metabolic, structural malformation of brain or mitochondropathy was entertained and accordingly investigated. MRI was suggestive of Leighs Disease and his CSF lactate levels were high. This case is presented to highlight that in case of absence of infection, metabolic encephalopathy or mitochondropathies can be thought as a cause of Encephalopathy